The revised definition of pulmonary hypertension: exploring the impact on patient management - Gérald Simonneau; Marius M. Hoeper (2019)
At the 6th World Symposium on Pulmonary Hypertension (PH), it was proposed that the mean pulmonary arterial pressure (mPAP) threshold used to define PH should be lowered from ≥25 mmHg to >20 mmHg. The rationale for this change is that the ≥25 mmHg threshold is arbitrary, whereas the revised threshold is based on scientific evidence. For the definition of all forms of pre-capillary PH, the inclusion of a pulmonary vascular resistance (PVR) ≥3 Wood Units was also proposed, placing greater emphasis on an elevated PVR to identify pulmonary vascular disease. Here, we discuss the possible impact of the revised definition of PH on future clinical management. This change may facilitate earlier PH detection, particularly in at-risk patient groups that are already undergoing screening programmes, e.g. those with systemic sclerosis or mutations associated with PH. As an mPAP above the upper limit of normal (>20 mmHg) but <25 mmHg is associated with increased risk of morbidity and mortality compared with a normal mPAP, early identification of patients in this group is important to enable close monitoring and timely treatment initiation once clinically indicated. Treatments currently approved for PH are not necessarily suitable for patients with an mPAP 21-24 mmHg, as the management of this group has not been widely examined. The revised definition may facilitate inclusion of these patients in prospective trials, allowing the evaluation of appropriate management strategies.